Desialylated low density lipoprotein - naturally occurring modified lipoprotein with atherogenic potency - Orekhov, Alexander N.; Tertov, Vladimir V.; Mukhin, Dmitry N. (Atherosclerosis, 1991)
We have recently established that low density lipoprotein (LDL) of most patients with coronary atherosclerosis differs from the LDL of most healthy subjects by its ability to cause primary atherosclerotic changes, i.e. the accumulation of intracellular cholesterol in the cells of smooth muscle origin cultured from unaffected intima of human aorta. Patients' LDL has a 2.5–5-fold lower content of sialic acid as compared with the LDL of healthy subjects. On the other hand, desialylation of native LDL with neuraminidase makes it capable of causing accumulation of intracellular cholesterol similar to patients' LDL. In the present study we showed that LDL of patients and healthy donors did not differ in the content and composition of protein and lipids. Thus, the difference in the content of sialic acid is the only difference observed between atherogenic LDL of patients and nonatherogenic LDL of healthy donors. A low content of sialic acid is characteristic of both protein and lipid moiety of LDL particle. Sialic acid content was determined in individual LDL preparations obtained from patients and healthy donors. The sialic acid of LDL preparations of 25 out of 27 patients was below 18 μg/mg protein. LDL from 2 patients with higher sialic acid content proved to be normal. The ability of patients' LDL and LDL desialylated with neuraminidase in vitro to cause the accumulation of intracellular lipids correlated with the degree of lipoprotein desialyation. Apparently, the ability of patients' LDL to stimulate the cellular lipid accumulation may be explained by a deficiency of sialic acid in the lipoprotein particle.